A Literary Turn in African Studies - Kelvin Acheampong (The Thinker)
The literary turn in African Studies is conceptualized here not as entailing the shift to textual/ discourse analysis pioneered by Edward Said, but as how African literary figures have contributed to the advancement of decolonization/ decoloniality in African Studies. Its point of departure is the “decolonial turn”, which refers to the varied patterns of decolonial thought emerging from different geographic and epistemic sites. Although there are sometimes divergences among these patterns of thought, the salient point of convergence is their acknowledgement of coloniality as a problem haunting the world today, and of the task of decolonization/ decoloniality as unfinished. There is, however, a tendency among certain scholars to trace the genealogy of decolonial thinking, ignoring the various contributions to decolonial thinking from other sites. This article attempts to fill this crucial gap by accounting, specifically, for an African literary genealogy of decolonial thinking through the lens of the concept of “generations.” The ideas of generations and turns in literary studies in particular, and African Studies in general, are complicated by the overlapping ideological dispositions of the writers.